Semisynthesis and neurotrophic activity studies of novel neomajucin/majucin derivatives as neurotrophin small molecule mimetics. (15th March 2022) - Yang, Ruige; Fu, Yingying; Chu, Junyan; Hu, Feixia; Zheng, Shudan; Wang, Lei; Liu, Mengqi; Liu, Jifeng
Graphic abstract: Highlights: Three series of novel neomajucin/majucin based esters were prepared. The spatial structures of 1g and 3c were unambiguously determined by X-ray crystallography. Compounds 1a, 1j, 1r, 2b, 2d, 3a, 3b, 3d and 3h displayed more potent neurite outgrowth-promoting activity than their precursors. Compounds 1a and 3a exhibited relatively no cytotoxicity to normal H9C2 cells. Abstract: Majucin-type Illicium sesquiterpenes with potent neurotrophic activity are considered to be promising candidates for the treatment of various neurodegenerative disease. Owing to the low-abundance metabolites in Illicium genus, there are few studies on their structural modifications, structure-activity relationships, and pharmacophoric motif. Herein, structural modifications were conducted on the hydroxyl groups at C-3 and C-6 positions of two majucin-type compounds neomajucin (1 ) and majucin (2 ), and 39 neomajucin/majucin based esters were synthesized and evaluated for their neurite outgrowth-promoting activities. Among all the target derivatives, compounds 1a, 1j, 1r, 2b, 2d, 3a, 3b, 3d and 3h displayed more potent neurite outgrowth-promoting activity than their precursors. Some interesting structure–activity relationships (SARs) were also observed. Moreover, compound 1a showed good neuroprotective effect on MPP + -induced PC12 cell damage. Finally, compounds 1a and 3a exhibited relatively no cytotoxicity to normal human H9C2 cardiac cells. This work will shed light on the development of neomajucin/majucin derivatives as potential neurotrophic agents.